Raumfunktionelle Prinzipien in einer allgemeinen theoretischen Geographie: Axiomatische und empirische Bestandteile in ihr - Tschierske, Hilmar (ERDKUNDE, 1961)
From a clarification of basic geographical concepts, depending whether they are of empirical origin, e. g. landscape, complex, or axiomatically derived as the underlying principle of any kind of mapping, distribution, interrelationship, etc., the two following possibilities appear: 1st to see the basic geographical concepts as part of a logically linked system in which case it hinges on an axiomatic not an empirical concept; 2nd to discover and grasp the possibility and existence of a general theoretical geography which aims towards gaining and formulation of general laws and regularities whose contents are not specific or empiric but general and formal; they are called general since they are valid for all phenomena which have distributions. These two possibilities of logic development lie in the direction of development in which C. Troll used the expression space functional principles (Raumfunktionelle Prinzipien) and at whose end there should be a general theory of these principles.